Study on the effects green building and conventional building on occupants' perceived comfort and satisfaction levels in Singapore - Li, Zhe. (2009)
This research looked into the comparison of the effects green building and conventional building on occupants’ perceived comfort and satisfaction levels and evaluated the buildings’ indoor environments in terms of room temperature, lighting, air quality, acoustics, ventilations, and workers’ productivity. Through conducting surveys among occupants on their comfort and satisfaction level of one green building and one conventional building; Many evidence were found to prove that green building is more comfortable and health beneficial than conventional building. However by grouping people according to their age, gender and years of working, the findings differed a lot among different groups. Certain groups of people in green building even gave lower ratings on some indoor environmental quality categories than the same groups from the conventional building. Therefore, although the green building generally possesses better indoor environment quality than conventional buildings, not all of the occupants perceived the comfort in the same way. Different groups’ people have their own focuses on specific factors of indoor environmental quality, and the effects indoor environment on them also vary among different groups. My result suggested a need to improve indoor air quality, room temperature, and some smart strategies to enhance the sound privacy of cubicle offices layout in both green and conventional building.